GeSn Nanobeam Light-Emitting Diode as a GHz-Modulated Light Source - Ricky Gibson; Joshua Hendrickson; Richard A. Soref (IEEE Photonics Journal)
Designs and theoretical analysis are presented for a room temperature resonant-cavity-enhanced GeSn LED whose emission peaks at the 2 $μ$ m wavelength. The Ge/GeSn/Ge PIN hetero-diode of length 1 $μ$ m is embedded in a rib-type Ge-on-Si nanobeam having either 24 or 36 air holes. The maximum LED modulation bandwidth $f_{3\text{dB}}$ is proportional to the Purcell factor and is inversely proportional to $τ _{s\,p0}$ the GeSn bulk spontaneous emission lifetime. For an emission linewidth of 200 nm and $τ _{s\,p0}$ of 10 ns, an $f_{3\text{dB}}$ of 1.6 GHz is predicted.